Konsep Keadilan Ekonomi Islam Dalam Sistem Ekonomi: Sebuah Kajian Konsepsional - Indra Sholeh Husni Husni (Faculty of Economics and Management, 2020)
Justice is a benchmark in an economics system. In the application of the modern economic system like the capitalist economic system and the socialist economic system, there are many injustices to the people. Problems that make it unfair are, many social inequalities between communities it makes a lot of poverty or unemployment in the country. Therefore, we need an economic system that canbe a solution for people’s welfare, we call with Islamic Economics System. The type of this research is library research category, it’s a research by using the literature. The writing method is descriptive qualitative by using a primary reference source and processing research materials in the library like a book, news, and others.The purpose of this research is to discuss the concept of justice and the application of justice concepts in the economic system, especially in Islamic economics. From the discussion that has been done in this research, we can conclude that the concept of justice has two contexts, both are the individual context and the social context. As the individual context, in the Muslim activity of economics, they must not hurt themself. But in the social context, every Muslim requiredto not fool the others. The application of the justice concept in Islamic economics system is nothing of economic inequality between one person and another person. The Islamic economics system also prohibits any kind of injustice economics like monopoly and concentration of economic power in one particular group or person. Also with the capitalist system and the socialist system which tends to not prosper the community in the country.